Education and everyday life: McLuhan's 'city as classroom' as a practice of social justice in social change. Issue 2 (3rd April 2018) - Dowd, John
ABSTRACT: In this article, I argue that Marshall McLuhan's underexplored notion of the 'City as Classroom' can provide a robust model of education that can serve as an important foundation for social justice and civic action. Infusing McLuhan's model with conceptual insights from critical pedagogy, I offer a situated education of everyday life that allows for creative and adaptive resources for navigating broader fields of power in a variety of socio-cultural contexts.